Fludarabine-treosulfan compared to thiotepa-busulfan-fludarabine or FLAMSA as conditioning regimen for patients with primary refractory or relapsed acute myeloid leukemia: a study from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation (EBMT) - Saraceni, Francesco; Bochtler, Tilmann (Journal of hematology & oncology, 2019)
Limited data is available to guide the choice of the conditioning regimen for patients with acute myeloid leukemia (AML) undergoing transplant with persistent disease.
Gesehen am 17.07.2019